2019
DOI: 10.1089/tmj.2018.0034
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Mobile Oral Health Application for Preschoolers

Abstract: The application was successful regarding the following three assessed attributes: (1) effectiveness, (2) efficiency, and (3) satisfaction. However, dietary education was observed to be necessary for the children and their guardians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 22 publications
0
25
0
8
Order By: Relevance
“…In oral health field, some apps have used games to teach children a wide range of topics including tooth decay, healthy and carcinogenic diet. [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In oral health field, some apps have used games to teach children a wide range of topics including tooth decay, healthy and carcinogenic diet. [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of the full-text articles reviewed, 11 were excluded because they were not SGs, 6 were not SGs in dentistry, 3 were secondary studies, and 1 paper was in French language. 3,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] In addition, six studies were identified by 6,12,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] corresponding to 19 studies, were included, because six studies were reported more than once. [54][55][56][57][58][59] Figure 1 shows the flow diagram of the selection process of our review.…”
Section: Resultsmentioning
confidence: 99%
“…About half of the SGs (n = 9) were developed in Brazil, 12,38,39,41,44,[47][48][49][50] three in the United Kingdom, 43,51,52 two in Taiwan, 37,45 and two in the United States. 6,53 A smaller number (n = 1) were developed in Germany, 46 Spain, 42 and South Africa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of methods, other research combines the application with other available applications such as open maps and websites integrated with the applications [7].Another study aiming to develop a smartphone application for pre-school children uses a different method based on an interactive children's book flux design [8].The different methods can occur due to different development goals and application development targets in specific population with different characteristic.…”
Section: Related Work/literary Reviewmentioning
confidence: 99%